Expression of costimulatory molecule CD70 is prognostic in small cell lung cancer - David Dora; Zsolt Megyesfalvi; Imre Vörös; Ágnes Paál; Peter Takacs; Daniela Dobos; Bence Lőrincz; Syeda Mahak Zahra Bokhari; Kenan Aloss; Gergely Pallag; Christopher Rivard; Hui Yu; et al. (Cancer Immunology, Immunotherapy)
Abstract Introduction Small cell lung cancer (SCLC) is a highly aggressive malignancy with poor survival outcomes. The CD70-CD27 axis has been implicated in immune regulation and tumor progression across cancers, but its role in SCLC has not yet been elucidated. This research explores the expression patterns and prognostic significance of CD70 and CD27 in early-stage SCLC. Methods In this retrospective study, we analyzed 190 surgically resected SCLC tumor samples using immunohistochemistry (IHC) for CD70 and CD27 expression and RNAscope for CD70 RNA detection. Immune infiltration was assessed using CD45, CD8, and CD20 staining. Quantification of RNAscope signals was performed using QPath software. Kaplan–Meier survival analysis and multivariate Cox regression were used to assess the prognostic impact of CD70, CD27, and immune cell infiltrates on overall survival (OS). Results CD70 was expressed in 46% of tumors, primarily within tumor nests, with lower expression in stromal areas. High CD70 expression correlated with significantly decreased OS (p = 0.0078, HR: 1.795) without any correlation with CD45 + , CD8 + or CD20 + immune cell infiltrates. CD27 expression was mainly confined to the stroma, and it did not show a significant association with OS (p = 0.582). Importantly, high CD27 expression was linked to reduced CD45 + and CD8 + cell densities in the stroma. Both CD70 and CD27 were expressed on CD68 + macrophages, CD27 was expressed on CAFs, and both molecules exhibited a partial coexpression with CD3. Furthermore, patients with high CD20 + B-cell densities or the presence of tertiary lymphoid structures (TLS) had significantly improved OS (p = 0.0017, HR: 0.491), suggesting the importance of B-cell-related immune responses in SCLC prognosis. Conclusion CD70, B-cell density and the presence of TLSs, but not CD27, emerged as a significant prognostic biomarker for OS in surgically treated SCLC, suggesting its potential as a therapeutic target.